A multidimensional analysis of older adults wellbeing and health literacy in Alentejo: a cross-sectional study - Sadio, Rute; Henriques, Adriana; Nogueira, Paulo; Costa, Andreia (Frontiers in Public Health, 2025)
IntroductionThe global increase in the older adults population which represents 22% the population in Portugal and is especially pronounced in the Alentejo region, posed noteworthy challenges. Social isolation, particularly in rural areas, requires policies that promote inclusion and wellbeing, such as social prescription. This study aimed to conduct a multidimensional assessment of the older adults individuals in Alentejo, evaluating quality of life, wellbeing, functionality, loneliness and health literacy.MethodsA cross-sectional design was performed involving 344 participants aged 65 and over, residing in the Alentejo region. Validated scales and Questionnaires were used to assess sociodemographic characteristics, quality of life, wellbeing, functionality, loneliness and health literacy. Data were analyzed using SPSS software, employing descriptive and inferential statistics to identify significant patterns and relationships between variables.ResultsThe sample consisted of 52% women, with an average age of 75.3 years (SD = 7.31; range = 65–96 years). Wellbeing, as measured by the WHO-5 index, was preserved with an average score of 53 (SD = 4.29). Loneliness was prevalent, with 50% of participants experiencing it, and the average score on the UCLA Loneliness Scale was 41.9 (SD = 5.59). Pain and anxiety were the most commonly reported issues according to the EQ-5D-3L, with 57.3% reporting pain/discomfort and 48.5% reporting anxiety/depression. Health literacy levels were low, with, only 6.4% exhibiting excellent literacy, while 45.0% had problematic or inadequate literacy.DiscussionThe findings suggest that while preserved, significant differences exist between men and women, as well as between rural and urban residents. Mobility, pain, and anxiety were the primary factors affecting Quality of life, particularly in rural areas. Low health literacy was identified as a barrier to autonomy and effective health management, emphasizing the need for tailored interventions to promote active and healthy aging.